Shifts in small-scale fishing in Åland : An overview of changes in regulations, catches and livelihoods between 2008 and 2025 - Svels, Kristina; Eriksson, Viktor; Sundström, Linda; Salmi, Pekka (Luonnonvarakeskus, 2025)
Almost two decades have passed since Erik Neuman wrote the report "Fishing and Fisheries Management in the Åland Archipelago" (2007). However, since 2007 many economic, societal and environmental changes have taken place, motivating a new report to be compiled that examines, not only the commercial fisheries sector, but also addresses issues related to recreational, household, and tourism fishing. Data is compiled from structured interviews, Q-method analysis, work-shops, document analysis and a survey to water-owners. The report provides an overview of key topics including the structure and governance of the Ålandic fisheries sector and regulation of small-scale fisheries. It presents major species such as perch, pike-perch, herring, whitefish, salmon, and cod and analyses quotas, fish stock monitoring and user rights. The report looks at the roles, challenges and opportunities for a broad fisheries sector, highlighting a decline in commercial fishing and the increasing complexity of fishery management and water ownership. Issues with grey seals and cormorants are discussed from an Ålandic perspective. Based on the findings, this report proposes several recommendations for the Government of Åland to consider, including strategic planning and policy development; collaboration and stakeholder engagement; fisheries management and conservation; and support for commercial fishers, economic development, and market expansion. The results show that Åland’s fisheries sector, deeply rooted in the islands’ cultural heritage, faces growing challenges from environmental pressures, regulatory changes, and societal shifts making it harder for commercial fishers to maintain their livelihoods. The decline in the number of commercial fishers has also weakened traditional practices and knowledge. Issues like eutrophication, water conservation, and increasing seal and cormorant populations add further strain on all fishers. The absence of a comprehensive fisheries strategy highlights the need for long-term, integrated solutions. Despite this, opportunities for fishers remain. While some collaboration exists, such as between water commons on licenses, environmental projects via the Fisheries Local Action Group and Leader program, and recent government initiatives on recreational fisheries, a broader and stronger cooperation is needed. Addressing the challenges requires not only policy adjustments but also a renewed recognition of the social and cultural value of the broader fisheries sector. By fostering co-creative governance and strengthening the fishers’ representation in decision-making on the Ålandic national level, the sector can ensure the resilience of its fishers and safeguard its fisheries cultural and economic future. This report is written within the realm of the Horizon Europe “Socio-economic Empowerment of coastal communities as users of the sea to ensure sustainable coastal development” (EmpowerUs) project 2022–2025.
Keywords: Åland; commercial fishing; household fishing; recrerational fishing; tourism fishing; water ownership; water commons; owner-based resource management; cultural heritage